Analysis of the Elementary School Students Difficulties of in Solving Perimeter and Area Problems - Abadi, Muhammad Arya Setiawan; Amir, Mohammad Faizal (Universitas PGRI Madiun, 2022)
The purpose of this study was to analyze the types (concepts, principles, and verbal) and forms of difficulties that elementary school students did in solving problems of perimeter and area of plane figures based on their level of completion ability. This research method is qualitative with a case study type. The technique of taking research subjects used purposive sampling by selecting three subjects of fifth-grade elementary school students based on the level of mathematical ability (low, moderate, and high) in solving perimeter and area of plane figures. Data collection techniques using tests and interviews. Data analysis techniques include data reduction, data presentation, and concluding. The results showed that students with low levels of ability experienced verbal difficulties in not working on the questions according to the instructions. Students with a moderate level of ability face conceptual difficulties in the form of being unable to make relevant decisions according to the requirements of the questions. In addition, students experience principle difficulties in the form of an inability to determine the relevant factors and incorrectly using the perimeter unit for the area unit. Students with a high level of ability experience principle difficulties in using formulas, so they tend to experience inaccuracies in solving problems. Other findings in this study provide that elementary school students have difficulty solving problems of perimeter and area of a plane figure because of basic problems, namely experiencing obstacles in verbal problems and inadequate conceptual knowledge.